2017
DOI: 10.1002/jia2.25020
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevention where it is needed most: comparison of strategies for the geographical allocation of interventions

Abstract: IntroductionA strategic approach to the application of HIV prevention interventions is a core component of the UNAIDS Fast Track strategy to end the HIV epidemic by 2030. Central to these plans is a focus on high‐prevalence geographies, in a bid to target resources to those in greatest need and maximize the reduction in new infections. Whilst this idea of geographical prioritization has the potential to improve efficiency, it is unclear how it should be implemented in practice. There are a range of prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…Mathematical models using local epidemiological and behavioral data provide insights on which approach would yield the greatest reduction of HIV-1 transmission [8] , [9] , [10] . Results from a modelling study using data from Nairobi suggested that, in a setting with limited resources, decreasing overall HIV-1 infections could best be achieved when male sex workers were prioritized for PrEP and ART initiation, followed by prioritizing MSM not reporting sex work and FSW [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models using local epidemiological and behavioral data provide insights on which approach would yield the greatest reduction of HIV-1 transmission [8] , [9] , [10] . Results from a modelling study using data from Nairobi suggested that, in a setting with limited resources, decreasing overall HIV-1 infections could best be achieved when male sex workers were prioritized for PrEP and ART initiation, followed by prioritizing MSM not reporting sex work and FSW [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Third, recommendations that come out of geospatial analyses should be translated into policy with caution. Oversimplification of geospatial conclusions may result in lower impact than the theoretical maximum [ 35 , 36 ] due to funds being trapped in allocations which are locally inefficient. Models may also be naive to the additional costs of changing intervention programs or implementing them only in certain regions or populations in a country.…”
mentioning
confidence: 99%
“…The observation of herd immunity in vaccinology suggests the importance of a uniform approach to prevention, even for HIV. In one mathematical model, if prevention resources were restricted to high-prevalence locations, 41% fewer infections would be averted than if resources were available at all locations regardless of HIV prevalence [ 26 ]. The desire for participants in our study to have their HIV prevention method blend into their lifestyle is an important concept for discussion, because it prompts a conversation about how HIV prevention methods could be developed to be widely palatable for a uniform, rather than a restricted, approach.…”
Section: Discussionmentioning
confidence: 99%